Broken discrete symmetries in a frustrated honeycomb antiferromagnet - Rosales, Héctor Diego (2013)
We study the magnetic phase diagram of the J1-J2 Heisenberg antiferromagnet on a honeycomb lattice at the strongly frustrated point J2/J1=1/2 using large-scale Monte Carlo simulations. At low temperatures we find three different field regimes, each characterized by different broken discrete symmetries. In low magnetic fields up to hc1/J1≈2.9 the Z3 rotational lattice symmetry is spontaneously broken while a 1/2-magnetization plateau is stabilized around hc2/J1=4. The collinear plateau state and the coplanar state in higher fields break the Z 4 translational symmetry and correspond to triple-q magnetic structures. The intermediate phase hc1<h<hc2 has an interesting symmetry structure, breaking simultaneously the Z3 and Z4 symmetries. At much lower temperatures the spatial broken discrete symmetries coexist with the quasi-long-range order of the transverse spin components.